THE INFLUENCE OF CONFUCIAN PHILOSOPHICAL THOUGHT ON THE FORMATION OF THE FOUNDATIONS OF CHINESE REPUBLICANISM - Sheviakov, Illia (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The role of Confucian principles in shaping Chinese governance is analysed, as well as the role of Confucianism, particularly the concept of the «Mandate of Heaven» as an instrument for legitimising political power. The influence of Confucianism on institutional mechanisms of governance in ancient China and the significance of Confucian principles as the philosophical framework of Chinese statehood during the imperial period are examined. The moral and ethical system created within Confucianism as the main instrument for regulating social relations in imperial China is examined. The conceptual foundations of the «Three Principles of the People» put forward by Dr. Sun Yat-sen as the basis of the Chinese understanding of republicanism are examined. The role of Confucianism as the ideological basis of Dr. Sun Yat-sen’s doctrine of the «Three Principles of the People» is studied. The influence of Confucianism on the Principle of «Nationalism» within Dr. Sun Yat-sen’s political theory and the role of moral and ethical principles in the formation of the nation is analysed. The interpretation of popular sovereignty in the context of Dr. Sun Yat-sen’s principle is analysed. The significance of meritocracy within Confucian philosophy and its role in the implementation of the «Principle of Popular Sovereignty» are studied. The duality between loyalty to the state and to the nation in Confucian thought, as reflected in the Principle of Nationalism, is analysed. The Confucian understanding of the role of the state in the economy within the framework of the Principle of «People’s Welfare» is examined. Discrepancies are identified between the interpretation of the economy’s legitimising function in the «Three Principles of the People» and in Confucian philosophy. The role of the state in providing infrastructure and preventing natural disasters within the framework of Confucian philosophy and its reflection in the «Principle of People’s Welfare» are analysed. The significant role of Confucianism in each of the «Three Principles of the People» and its influence on the Chinese interpretation of republican ideas is noted. In this context, the moral, ethical and philosophical foundations of Confucianism serve as a framework for interpreting traditionally Western concepts such as «nationalism» and «democracy». The study concludes that Confucian philosophical thought exerts an ambivalent influence on the «Three Principles of the People» put forward by Dr. Sun Yat-sen.